Bezoar z łez ludzkich czasu powietrza morowego by Walenty Bartoszewski as an Example of “A Prescription for the Soul and the Body” at the Time of the Plague - Kardasz, Monika (Tematy i Konteksty, 2021)
The article is an attempt to interpret a hardly known collection of poems by Walenty Bartoszewski, a Jesuit in Vilnius, published in reaction to the outbreak of the plague in Vilnius in the years 1629–1632, which constitutes the testimony of increased religiousness in the face of an epidemic. In the article, the author of the collection is presented, as well as his poetic oeuvre. Also, a brief description of the social background of those events is given. Then, other texts from the 16th–18th centuries, concerned with the topic of the epidemic are characterized. They include sermons, secular works, religious songs and prayers. The main part of the article is devoted to the interpretation of the collection by Bartoszewski in the context of the most important aspects of the volume Bezoar z łez ludzkich czasu powietrza morowego [Bezoar of Human Tears Shed at the Time of the Plague], which include: the manifestation of religiousness at the beginning of the 18th century, the realities of the epidemic depicted in lyrics, the vision of God and Christ, ways of protecting the faithful against the plague, and the intercession of the Mother of God.